(untitled) (Raparin Journal of Humanities (RJH), 2019)
The development of technology, information technology and various means of communication have a significant impact on public relations activity; especially in government institutions. Many government institutions have invested these means in their management system, in order to facilitate the goals of the institution, and ultimately the interaction between the internal and external public. In this theoretical research, I tried to explain the impact of the new media on public relations in the public administration, based on the views of specialists. The aim of the research is to know the use of the new media of public relations and how in the system of public administration, as well as, Explaining the role it plays in public relations activities of government institutions. Add to this, analyzing the way of how new media and public relations participate in the birth of e-government. In the results, it is clear that the new media has facilitated public relations between the public and other institutions, as it strengthened relations between them